Characterization of micro-components of avocado oil extracted with supercritical carbon dioxide and their effect on its oxidative stability - Duodu, Kwaku Gyebi (University of Pretoria, 2013)
Thesis (PhD (Food Science))--University of Pretoria, 2008.